Selective synthesis of 4-hydroxyisophorone and 4-ketoisophorone by fungal peroxygenases. Issue 6 (26th February 2019) - Aranda, Carmen; Municoy, Martí; Guallar, Víctor; Kiebist, Jan; Scheibner, Katrin; Ullrich, René; del Río, José C.; Hofrichter, Martin; Martínez, Angel T.; Gutiérrez, Ana
Abstract : Some fungal peroxygenases (UPOs) selectively oxidize α-isophorone to 4-hydroxyisophorone (4HIP) and 4-ketoisophorone (4KIP) while others are less selective or unable. Abstract : The recently discovered unspecific peroxygenases (UPOs) from the ascomycetes Chaetomium globosum and Humicola insolens were capable of selectively hydroxylating isophorone to 4-hydroxyisophorone (4HIP) and 4-ketoisophorone (4KIP), which are substrates of interest for the pharmaceutical and flavor-and-fragrance sectors. The model UPO from the basidiomycete Agrocybe aegerita was less regioselective, forming 7-hydroxyisophorone (and 7-formylisophorone) in addition to 4HIP. However, it was the most stereoselective UPO yielding the S -enantiomer of 4HIP with 88% ee. Moreover, using H. insolens UPO full kinetic resolution of racemic HIP was obtained within only 15 min, with >75% recovery of the R -enantiomer. Surprisingly, the UPOs from two other basidiomycetes, Marasmius rotula and Coprinopsis cinerea, failed to transform isophorone. The different UPO selectivities were rationalized by computational simulations, in which isophorone and 4HIP were diffused into the enzymes using the adaptive PELE software, and the distances from heme-bound oxygen in H2 O2 -activated enzyme to different substrate atoms, and the corresponding binding energies were analyzed. Interestingly, for process upscaling, full conversion of 10 mM isophorone was achieved with H. insolens UPO within nine hours, with total turnover numbers up to 5500. These biocatalysts, which only require H2 O2 for activation, may represent a novel, simple and environmentally-friendly route for the production of isophorone derivatives.